2017
DOI: 10.22159/ijpps.2017v9i12.19032
|View full text |Cite
|
Sign up to set email alerts
|

Structure Characterization and Evaluation Potential of Antimicrobial Extracts From Phellinus Linteus Against Skin Infectious Pathogens, Staphylococcus Epidermidis Atcc12228 and Propionibacterium Acnes Dmst14916

Abstract: Objective: The objective of this study was to investigate the antimicrobial activity of Phellinus linteus against skin infectious pathogens, Staphylococcus epidermidis ATCC12228 and Propionibacterium acnes DMST 14916. Methods:Fungal fruiting bodies were extracted with 95% ethanol and ethyl acetate, and then, vaporized. The antimicrobial activities were determined by the disc diffusion method against Propionibacterium acnes DMST 14916 and Staphylococcus epidermidis ATCC12228 skin infectious pathogens. A minimum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…This study demonstrated that most of these pathogens isolated from clinical samples were MDR, and those are potentially enough to destroy the clinical totem pole of a hospital and to precipitate devastating episodes in the community. As analyzed, suppurative infections are one of the major problems of health, as MDR bacteria could attack several organs such as lungs, heart, and kidneys, through BSI [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…This study demonstrated that most of these pathogens isolated from clinical samples were MDR, and those are potentially enough to destroy the clinical totem pole of a hospital and to precipitate devastating episodes in the community. As analyzed, suppurative infections are one of the major problems of health, as MDR bacteria could attack several organs such as lungs, heart, and kidneys, through BSI [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…MICs were determined to evaluate the antimicrobial activity of synthesized compounds [26,27]. A pure culture of a single microorganism was grown in Mueller-Hinton broth (MHB).…”
Section: Antimicrobial Studiesmentioning
confidence: 99%
“…The bacterial strains were grown on 5% nutrient broth (NB) and after initial incubation, organisms were suspended in 15 ml of NB and optical density was measured. The readings were compared with 0.5 McFarland standard [11]. For the determination of MIC, bacterial suspension at 5×10 6 colony-forming units (CFU)/ml was employed [12].…”
Section: In Vitro Antibacterial Assaymentioning
confidence: 99%